STATUS OF TRACE ELEMENTS (IRON, ZINC AND COPPER) IN SERA OF PREGNANT WOMEN AT THIRD TRIMESTER - HAWWAL RASOOL, SHELAN; ABDULLAH, AHED NAJIMELDDIN; LAZGIN BARANY, QAYS; SALIM AL-NAEMY, RAED (Journal of Duhok University, 2019)
Background and Objectives: Pregnancy is a biological phenomenon associated with dynamic changes in physical, mental and biochemical alterations in body. Maintaining the appropriate micronutrient levels is considered essential for developing the normal pregnancy otherwise there would be adverse pregnancy outcomes. Anemia is one of the most common public health problems in all trimesters of pregnancy where it is regarded as one of the most common causes of maternal death. The aim of this study is to evaluate the serum level of iron, zinc and copper at the third trimester of pregnancy and to ascertain the association between trace elements and hematological parameters.Methods: This cross sectional study was conducted in January - August 2018.  Study participants were divided in to two groups and each group consists of 40 pregnant women at their third trimester of pregnancy. The study group consists of women who did not take iron and folic acid supplements whereas the control group represented pregnant women who took iron and folic acid supplements (400 µg/day). Both zinc and copper were assayed using atomic absorption method whereas iron was measured manually using spectrophotometric method. Statistical analysis for all study variables was done using SPSS version 18. All variables were expressed as mean ± standard deviation (SD) and p values of 0.05 or less were considered statistically significant.Results: Mean serum iron level was statistically significantly lower in study subjects compared with controls (p = 0.01). Moreover, mean serum zinc concentration displayed a highly statistically significantly lower values in study subjects compared to controls (p < 0.0001). However, mean serum copper level was slightly lower in study group but did not show any statistically significant differences. No significant correlation seen between iron with zinc and copper and iron with hematological variablesConclusion: Pregnant women who did not take iron and folic acid supplementation developed maternal anemia as well as hypozincemia particularly in the third trimester. Therefore, sufficient intake of iron and zinc supplementation and trace metals rich diet during pregnancy is recommended to prevent adverse pregnancy outcomes.